Dissecting the Foundations of the Philosophy of Science: Ontology, Epistemology, and Axiology in a Contemporary Perspective - Rifqi, Ahmad; Dewi, Eva; Aziz, Muhammad Zaky (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The purpose of this study is to know and understand three important studies in the philosophy of science, namely ontology, epistemology, and axiology. Which Until now the study of philosophy of science is still the main concern. The existence of a philosophy of science that results from thinking activities is a pillar of civilization. where humans find themselves, understand the meaning of life, and live a more ideal life. This study reviews previous studies such as journal articles, books, and other academic sources that address similar topics to gain a better understanding of Science in Philosophy Review: Axiology, Ontology, and Epistemology. With the results, the three main components of the study of philosophy of science are ontology, epistemology, and axiology, as mentioned earlier. It has a very important role to understand the philosophy of science as a whole.